THE ACCURACY ANALYSIS OF LIDAR-DERIVED ELEVATION DATA FOR THE GEOMETRIC DESCRIPTION OF CROSS-SECTIONS OF A RIVERBED - G. Caroti; F. Camiciottoli; A. Piemonte; M. Redini (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2014)
The work stems from a joint study between the Laboratory ASTRO (Department of Civil and Industrial Engineering – University of Pisa), the municipality of Pisa and the province of Arezzo on the advanced analysis and use of digital elevation data. Besides, it is framed in the research carried on by ASTRO about the definition of the priority informative layers for emergency management in the territory, as of PRIN 2008. Specifically, this work is in continuity with other already published results concerning rigorous accuracy checks of LIDAR data and testing of the procedures to transform raw data in formats consistent with CTR and survey data. The analysis of sections of riverbed, derived from interpolation by DTMs featuring different grid density with those detected topographically, is presented. Validation by differential GNSS methodology of the DTMs used showed a good overall quality of the model for open, low-sloping areas. Analysis of the sections, however, has shown that the representation of small or high-sloping (ditches, embankments) morphological elements requires a high point density such as in laser scanner surveys, and a small mesh size of the grid. In addition, the correct representation of riverside structures is often hindered by the presence of thick vegetation and poor raw LIDAR data filtering.